(untitled) (AYUSHDHARA, 2018)
The geriatric population is highly prone to decreased quality of life, stress along with various other issues. There is a greater risk involved when it comes to both communicable and non-communicable diseases. With rapid urbanisation the elderly face age related psychological and physiological issues. The aim of the present study is to evaluate the change in Quality Of Life (QOL) and Perceived Stress (PS) when the old destitute women were subjected to practice of Integrated Approach of Yoga Therapy. A pre-post study was conducted. The Yoga module included loosening exercises, breathing practises, Asanas, Pranayama, MSRT Meditation, Bhajans. The data collected was assessed after 2 months of Yoga intervention. The questionnaire used were WHO QOL-BREF and PSS. The Yoga group reported reduction in Perceived Stress Scale score and increase in score in 3 domains of Quality Of Life Questionnaire namely Physical parameter, Psychological parameter and Environment parameter. There was a marginal decrease in the score of social relationship domain of Quality Of Life Questionnaire. Hence destitute women showed marginal improvement in QOL and PSS. However, additional research and long term yoga intervention is needed to further evaluate the efficacy of yoga to improvise the QOL and stress levels.